2016
DOI: 10.1063/1.4961749
|View full text |Cite
|
Sign up to set email alerts
|

Coupled wave equations theory of surface-enhanced femtosecond stimulated Raman scattering

Abstract: We present a coupled wave semiclassical theory to describe plasmonic enhancement effects in surface-enhanced femtosecond stimulated Raman scattering (SE-FSRS). A key result is that the plasmon enhanced fields which drive the vibrational equation of motion for each normal mode results in dispersive lineshapes in the SE-FSRS spectrum. This result, which reproduces experimental lineshapes, demonstrates that plasmon-enhanced stimulated Raman methods provide unique sensitivity to a plasmonic response. Our derived S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 37 publications
4
29
0
Order By: Relevance
“…The exact nature of the mechanism that underpins the lineshapes in SE-SRS is currently a topic of study. 108,204206 …”
Section: Bulk Ensembles To Single Moleculesmentioning
confidence: 99%
“…The exact nature of the mechanism that underpins the lineshapes in SE-SRS is currently a topic of study. 108,204206 …”
Section: Bulk Ensembles To Single Moleculesmentioning
confidence: 99%
“…In Ziegler's theory, the interference between Raman susceptibility and a stimulated surface plasmon emission results in asymmetric line shapes, and the increasing enhancement factors result in increasing dispersive line shapes [16]. In Schatz's theory, the Fano parameter depends on the ratio between the real part and the imaginary part of the square of the plasmonic field enhancement factor [17]. Different from Schatz's and Ziegler's work, our model makes an important prediction about the plasmonic enhancement factor which is given by F S | 2 F P and F P | 2 F S for PESRL and PESRG, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Ziegler et al indicated that the cross term between the heterodyned SE-FSRS signal and the plasmon light emission resulted in the dispersive-like line shape [16]. Schatz et al proposed that the asymmetric line shape resulted from the combination of two Fano contributions arising from the interference between both the real and imaginary components of the Raman local electromagnetic field and the plasmon field [17]. Both theoretical descriptions were based on reported SE-FSRS results and only discussed the SRG process.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative stimulated Raman technique is SE-FSRS, which was first introduced in 2011 by Frontiera et al [142]. The SE-FSRS signals have Fano line shapes, which result from coupling between the broadband plasmonic response from colloidal nanoparticles and the narrowband vibrational coherences in the molecular adsorbates ( Figure 9D) [140,143,144]. Interestingly, the vibrational coherence's dephasing time was independent of the coupling between the plasmon and the molecule [140].…”
Section: Ultrafast Sersmentioning
confidence: 99%